The Effects of Tax Competition when Politicians Create Rents to Buy Political Support - Wolfgang Eggert; Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2007)
We set up a probabilistic voting model to explore the hypothesis that tax competition improves public sector efficiency and social welfare. In the absence of tax base mobility, distortions in the political process induce vote-maximising politicians to create rents to public sector employees. Allowing tax base mobility may be welfare-enhancing up to a point, because the ensuing tax competition will reduce rents. However, if tax competition is carried too far, it will reduce welfare by causing an underprovision of public goods. Starting from an equilibrium where tax competition has eliminated all rents, a coordinated rise in capital taxation will always be welfare-improving. For plausible parameter values it will even be welfare-enhancing to carry tax coordination beyond the point where rents to public sector workers start to emerge.
Keywords: D72; D73; H87; 330; tax competition; rent seeking; probabilistic voting; Steuerwettbewerb; Steuerharmonisierung; Rent-Seeking; Wahlverhalten; Öffentliche Güter; Soziale Wohlfahrtsfunktion; Theorie